The Effect of Workload and Financial Rewards on Employee Performance Through Job Satisfaction at Guido Valadares National Hospital, Timor Leste - Teofilo Sebastiao Sarmento; Dewi Yustiana (SEAN Institute, 2026)
This study aims to examine the effect of workload and financial rewards on employee performance at Guido Valadares National Hospital, Timor Leste, with a focus on the mediating role of job satisfaction in these relationships. The research population consisted of all 45 employees of the hospital, with data collection conducted using a census sampling method. The collected data were analyzed using Partial Least Squares (PLS) methodology. The results indicate that workload has a positive and significant effect on employee performance, although this effect is not direct. Instead, it is mediated by job satisfaction. Employees who experience high levels of job satisfaction, even when faced with a heavy workload, tend to demonstrate better performance. In addition, financial rewards also show a significant positive effect on employee performance. Adequate financial recognition enhances job satisfaction, which in turn contributes to improved performance. Job satisfaction is proven to play a critical role as a mediator in both relationships. High levels of job satisfaction enable employees to manage high workloads effectively and improve their performance. Furthermore, job satisfaction strengthens the positive impact of financial rewards on employee performance, highlighting its central role in the organizational environment.